Analisis Pengaruh Iklan Boyband BTS sebagai Brand Ambassador terhadap Minat Beli pada Aplikasi GoFood - Aina Divany; Hosiana Arga Putri; Sholikah Desi Purwanti; Nur Aini Rakhmawati (Journal of Business and Economics Research (JBE), 2023)
Inside the increasingly globalized world, technological advancements have the potential to impact business sustainability. Approaches for resolving them including choosing the suitable advertisements and brand ambassadors and attracting consumers' buying interest. PT Gojek Indonesia or Gojek, one of Indonesia’s first online transportation service providers, also carried out a series of promotional activities through advertising to maintain and improve competitiveness and quality among many other business competitors. In June 2022, Gojek introduced BTS as their new brand ambassador through GoFood ads. When the chosen brand ambassador succeeds in attracting consumers, consumers’ buying interest will increase. Consequently, the the researcher is keen to know boyband BTS advertisements’ significance as a brand ambassador in terms of buying interest in the GoFood application. The primary data collection method was used through questionnaires on Google Forms. The collected records were then examined using a simple linear regression, using the SPSS 25. In accordance with the findings of the data analysis, the advertisement of the boyband BTS as a brand ambassador has a notable aftermath on buying interest in the GoFood application.